The influence of digital literacy initiatives in South Africa : a Nemisa case study - Moleko, Letlotlo Kenneth (My University, 2022)
The aim of the study the Influence of digital literacy initiatives in South Africa. The study focuses on the National Electronic Media Institute of South Africa (NEMISA which was initiated in 1998 with the core purpose of being an education, learning and technical skills centre for the Television, Radio and Broadcasting industries. Studies on the influence of digital literacy initiatives in South Africa are limited. Therefore, a need exists for a thorough understanding of these digital literacy initiatives' influence in improving economic and job opportunities for the target user groups. A qualitative case study research methodology was used to establish deeper insights and perspectives from multiple stakeholders to ensure a holistic and in depth view of these initiatives within their natural context. 14 individuals were interviewed and 6 of the of the respondents were current and former students of NEMISA. The research study adopted the Multiliteracies framework as a means for understanding how the evolution of technology impacts the learning context and identify ways to improve digital literacy in the cultural context of South Africa. The research study uncovered six key themes which comprised namely accessibility, e-learning, economic viability, future Skills, lifelong learning and partnerships. The results from this research revealed that digital literacy training provided by NEMISA improved the opportunity to gain job opportunities for students, improved access to institutions of further learning, and aided in motivating lifelong learning. The researcher recommends digital literacy to be introduced at basic, secondary and tertiary education levels
A dissertation submitted in fulfilment of the requirements for the degree of Master of Management in Digital Business to the Faculty of Commerce, Law and Management, School of Business Administration, University of the Witwatersrand, Johannesburg, 2022
Keywords: Digital literacy; Multiliteracies; Digital skills; E-learning; Lifelong learning; SDG-4: Quality education